ANALISA PENGENDALIAN BANJIR AKIBAT PELUAPAN DEBIT ALIRAN DENGAN PERKUATAN TEBING MODEL SHEET PILE Studi Kasus Sungai Batang Lumpo Kabupaten Pesisir Selatan - Muhammad Lubis, Nofrizal (Menara Ilmu, 2018)
Flooding ia caused by the increased volume of waterâ€™s volume in the river or lake so that water isout of its natural limits. The flooding is mostly caused by inadequate river capacity to accommodate riverdischarge. The amount of river discharge at the time of flood is caused by the increasing amount of surfacerunoff from the rains that fall in the catchment area. Based on the preliminary survey conducted, it was foundthat the frequency of flooding in the Batang Lumpo river area is 2-3 times a year with a height ranging from0.5 to 1.5 meters from the soil surface with the duration of inundation ranges from 4 to 6 hours. Areasaffected by flooding ranging from the area of Nagari Taratak Tengah Lumpo Kecamatan IV Jurai down tothe downstream river at Nagari Pasar Baru Kecamatan Bayang. By the result of the analysis obtained flooddischarge using Rational method Q 100 years = 237, 26 mÂ³ / dt, high h = 2.7 m, the high value of W = 1.16m length Sheet Pile in flood condition = 4.14 m, Maximum Moment Mmax = 6, 31 tm and sheet pile length indry condition = 3.16 m, Mmax Moment = 7,125 t.m.Keywords: Flood, Outflow discharge, Sheet Pile